Dance movement psychotherapy with people with learning disabilities out of the shadows, into the light - Unkovich, Geoffrey; Butté, Céline; Butler, Jacqueline (Routledge, 2017)
"This book provides an overview of dance movement psychotherapy for young people and adults with learning disabilities. Contributors from a variety of backgrounds examine their work with clients from across the disabilities spectrum, ranging from mild to complex needs.　The book chapters present theory and practice relating to the client group and subsequent therapy processes"--Provided by publisher.